Carbon emission assessment of wastewater treatment plant based on accounting perspective - Lin Lin (E3S Web of Conferences, 2020)
Excessive GHG emissions from human activities lead to climate warming, and sewage treatment plants are one of the sources of GHG emissions. The number of sewage treatment plants in my country is increasing year by year, and they emit a large amount of GHG, it is necessary to evaluate their emissions and seek ways to reduce emissions. According to the “Greenhouse Gas Inventory Protocol-Corporate Accounting and Reporting Standards”, taking a sewage treatment plant in a northern city as an example, the GHG emission classification of its operation control range, selection of evaluation methods and emission factors, assessment of GHG emissions, analysis of GHG emissions Constitution, propose ecological treatment technology, recycling CH4 and other emission reduction measures.